Community membership and reciprocity in lending: Evidence from informal markets - Tomy, Rimmy E.; Wittenberg-Moerman, Regina (Journal of Accounting and Economics, 2024)
We study credit access in informal economies where market institutions, such as financial reporting systems, auditing, and courts, are nonexistent or function poorly. Using the setting of a large bazaar in India, we find that community membership plays a vital role in access to credit. Wholesalers are more likely to provide credit and offer greater amounts of credit to within-community retailers, and are more lenient when these retailers are delinquent. Furthermore, wholesalers who lent preferentially to their community retailers pre-COVID are more likely to receive help from their community following the COVID-19–related income shock, particularly from same-community landlords and suppliers. Also, wholesalers with low endowments, those with greater within-community information flow about them, and those facing income shocks are more likely to provide preferential credit to their community retailers. Our findings are consistent with an indirect reciprocity mechanism explaining within-community credit flows.